Economics of corruption/edited by Ajit Mishra - "Mishra, Ajit (ed.)" (New Delhi, 2005)
This book consists of 15 readings on various aspects of corruption. Various sections cover the concepts, history and evolution, the causes for its existence and persistence, its consequences and finally combating corruption. The book deals primarily with the economic aspects of corruption, though political, social, and historical facets are touched upon wherever possible. Starting with Kautilya s Arthashastra to provide a historical flavour of corruption, the volume covers both individual behaviour and that of groups, classes and sub-cultures. While discussing the consequences of corruption on economic development, several readings focus specifically on India discussing aspects such as fiscal problems and informal black markets. Measures to combat corruption are also discussed by focusing on the incentives and institutional structures that are major factors in corruption.
Keywords: Economics